Shape-memory surface with dynamically tunable nano-geometry activated by body heat - Ebara, Mitsuhiro (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.